2015
DOI: 10.17344/acsi.2014.1071
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Application of PLS and PCR Methods to Simultaneous Quantitative Estimation and Simultaneous Dissolution Test of Zidovudine - Lamivudine Tablets

Abstract: In the development strategies of new drug products and generic drug products, the simultaneous in-vitro dissolution behavior of oral dosage formulations is the most important indication for the quantitative estimation of efficiency and biopharmaceutical characteristics of drug substances. This is to force the related field's scientists to improve very powerful analytical methods to get more reliable, precise and accurate results for the quantitative analysis and dissolution testing of drug formulations. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Chemometric calibration methods are observed that it is the best techniques to determinate the amount of each component in the complex mixture. The most accepted chemometric methods in drug analysis are principal component regression (PCR) and partial least squares regression (PLS) 4 .…”
Section: Ijpsr (2018) Volume 9 Issue 3 (Research Article)mentioning
confidence: 99%
“…Chemometric calibration methods are observed that it is the best techniques to determinate the amount of each component in the complex mixture. The most accepted chemometric methods in drug analysis are principal component regression (PCR) and partial least squares regression (PLS) 4 .…”
Section: Ijpsr (2018) Volume 9 Issue 3 (Research Article)mentioning
confidence: 99%